Microzonation of Seismic Vulnerability In Padang Panjang Timur Sub-District, Padang Panjang City Based on Microtremor Measurement - Elizha, Zellvia; Syafriani, Syafriani; Hamdi, Hamdi; Dwiridal, Letmi (Journal of Experimental and Applied Physics, 2024)
Padang Panjang City is one of the cities in West Sumatra which has a high level of risk of the natural phenomenon of earthquakes. This is due to the fact that it is traversed by the active Sumatran fault which can cause earthquakes at any time. The purpose of this study was to determine the value of the seismic vulnerability index in Padang Panjang Timur District, Padang Panjang City using microtremor measurements. This type of research is descriptive research, namely research that describes the symptoms or phenomena studied. The location for data collection was Padang Panjang Timur District, Padang Panjang City, West Sumatra Province. There are 15 data collection points, and the distance between points is 500 m. The microtremor method of measuring this microtremor can determine the dominant frequency value (f0), amplification factor (A0), and susceptibility index value (Kg). Microtremor data processing was used to obtain the H/V curve at each point of data collection using Geopsy software. The results of the microzonation of the seismic susceptibility index (Kg) ranged from 1.05 × 10-6 s²/cm to 170.09 × 10-6 s²/cm. High seismic vulnerability index values ​​are found in the Koto Panjang Sub-District, Tanah Pak Lambik Sub-District, Guguk Malintang Sub-District, Ngalau Sub-District and Ganting Sub-District.